Ultrawideband LNA 1960–2019: Review - Shahab Shahrabadi (IET Circuits, Devices and Systems)
Abstract To the best of the author's knowledge, several studies during 1960–2019 were carried out on wideband and ultrawideband LNAs just to render optimum LNAs for SAW‐less Radio‐Frequency Integrated Circuits (RFICs) but none of these works reviewed and taught the proceedings of these six decades, hence the lack of a comprehensive review is quite noticeable. This article specifically studies the challenges and solutions of designing UWB LNA by reviewing topologies and techniques such as inductive peaking, noise and distortion cancellation, gm‐boosting, active inductor and notch filter. Its historical aspect illustrates when the idea of wideband LNA was born and how it changed to ultrawideband LNA, and its tutorial aspect discusses circuits and achievements to present optimum LNAs in Complementary MOS (CMOS), BiCMOS and High‐Electron‐Mobility Transistor (HEMT) technologies. This work describes the endeavours of engineers in reaching UWB LNA from narrowband LNA during six decades that have great importance as a chapter in understanding this topic because it teaches all topologies, techniques, circuits and related events in a historical narrative for trained readers who are not experts on this topic.